Integration of migrants in Italy: local actors and African communities - Dömös, Mariann; Tarrósy, István (European Spatial Research and Policy, 2019)
Italy is undoubtedly one of the key actors in the current international “migration crisis” in the Mediterranean region. The paper aims to provide an overview of both the opportunities and problems for the Italian integration policy as of today. The authors intend to indicate the role of civil organisations in the ‘Italian migration issue’ and to emphasize the uniqueness of their initiatives. The study will provide an insight into one of the major immigrant communities, the Africans, through the civil organisations which have been working with them. The paper, based especially on empirical field experiences, is the result of a two-and-a-half-year research in Italy with different scholarships, coupled with other field trips in several sub-Saharan African countries.